Radiotherapy for T1‐2N0 glottic cancer: a multivariate analysis of predictive factors for the long‐term outcome in 1050 patients and a prospective assessment of quality of life and voice handicap index in a subset of 233 patients. (20th August 2013) - Al‐Mamgani, A.; van, P.H.; Woutersen, D.P.; Mehilal, R.; Tans, L.; Monserez, D.; Baatenburg de Jong, R.J.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the outcomes of patients with early stage glottic cancer (GC) treated with radiotherapy (RT). Design, setting and participants The current study report on a retrospective analysis of oncologic outcome of 1050 patients with T1‐2N0 glottic cancer treated with radiotherapy. Prospective assessment of quality of life (QoL) and voice handicap index (VHI) was performed in all patients treated from 2006 onwards (n = 233). Main outcome measures Local control (LC), regional control (RC), disease‐free survival (DFS), overall survival (OS), quality of life and voice handicap index. Results After a median follow‐up of 90 months (range 3–309), the actuarial rates of local control, regional control, disease‐free survival and overall survival were 85%, 99%, 84% and 81% at 5 years and 82%, 98%, 80% and 61% at 10 years, respectively. On multivariate analysis, T2 tumours, smoking after radiotherapy and conventional radiation scheme correlated significantly with poor local control. Patients who continued smoking after radiotherapy had also significantly lower overall survival rates (OR 4.3, P < 0.001). Hypothyroidism was reported in 18% of patients. Slight and temporary deterioration of quality of life scores was reported. Patient‐reported xerostomia and dysphagia at 48 months were −7.1 and −6.5, compared with baseline, respectively. Voice handicap index improved significantly from 37 at baseline to 18 at 48 months. Patients with T2b and those who continued smoking had significantly worse voice handicap index. Conclusions In the current study, excellent outcome with good quality of life and voice handicap index scores were reported. T2 tumours, in particular T2b, and continuing smoking after radiotherapy correlated significantly with poor local control and worse voice handicap index.